2021
DOI: 10.34006/jmbi.v10i2.290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Coal Export Development in Aceh Province Through Rca and Mci Approach

Abstract: This study aims to analyze  the development of coal’s export in Aceh Province by using Revealed Comparative Advantage (RCA) and Market Concentration Index (MCI). This study is descriptive quantitave research by using time series data for 6 years (2015 -2020), used data is value export of Aceh. RCA is used to analyze the competitive of coal, whereas, MCI is used  to analyze the ployment of coal’s export. RCA Index, since 2015 – 2019, is under 1 that means coal in Aceh has low competitiveness. RCA index in 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It was a positive to the mainly export value from the import percent, otherwise a negatively greater to imports than exports. Wherein to country or region was dominated by exports or imports (Khairina and Syahputra, 2021). Recently, other cases reported the export-import trade balance for the economic goods group of North Sumatra province from 2016 to 2019 tended to increase (Ginting et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It was a positive to the mainly export value from the import percent, otherwise a negatively greater to imports than exports. Wherein to country or region was dominated by exports or imports (Khairina and Syahputra, 2021). Recently, other cases reported the export-import trade balance for the economic goods group of North Sumatra province from 2016 to 2019 tended to increase (Ginting et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Nursodik et al (2021) supported this study result mentioned that tea, as one of the non-oil and gas commodities, had a strong comparative competitiveness and tend to be the exporter country to the international market on the stage of expanding export. Furthermore, previous research has revealed that coal commodities http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v11i2.24678 (Khairina & Syahputra, 2021) and furniture commodities (Elysi et al, 2018) also have strong comparative competitiveness in the international market. The TSR calculation result of Riniwati et al(2017) , also explained that fish and others commodities have TSR value close to 1.…”
Section: Lilis Yuliantimentioning
confidence: 99%
“…An empirical study in association with the non-oil and gas commodity analyzed by Khairina & Syahputra (2021) found that the coal commodity export was not quite spread and concentrated only in a single country. Indonesian coffee commodity in 2009-2018 was also not concentrated and specialized only in a specific region, as explained in the study of Kusmiati & Windiarti (2011).…”
Section: Introductionmentioning
confidence: 99%